Frontispiece: Fluorescence Colour Control in Perylene‐Labeled Polymer Chains Trapped by Nanotextured Silicon. Issue 11 (27th February 2022) - Takao, Ryota; Ushiro, Kenta; Kusano, Hazuki; Yuyama, Ken‐ichi; Shoji, Tatsuya; Linklater, Denver P.; Ivanova, Elena; Juodkazis, Saulius; Tsuboi, Yasuyuki
Abstract : Laser Chemistry In their Research Article (e202117227), Yasuyuki Tsuboi et al. report an optical tweezer technique using nanotextured Si that can efficiently trap polymer chains. The fluorescence color of the perylene‐labeled polymer chains can be controlled by changing the laser intensity.